BODY IMAGE THROUGH SILHOUETTE MATCHING TASK OF THIRD AGE FEMALE - Gonçalves, Glenda Lima; Barbosa, Rita Maria dos Santos Puga (Fiep Bulletin - online, 2011)
The objective of the present study was verifying the perception of elderly female's body image. This study characterizes itself as correlational-discriptive, with the sample of 30 academics Third Age women from UFAM, with ages between 60 to 85', selected randomly. For the measurement of the Body Image, it was used the Silhouette Matching Task, purposed by Stunkard et al. (1983) and adapted by Mash and Roche (1996), whereas the researches successively matched the observed body (OB), the real body (RB) and ideal (IB), appointed by the intervieweds. We concluded that 53.3% are satisfied with the Body Image silhouette, but there is a hypothesis that a body image distortion of those intervieweds exists, because their matched Real Bodies (RB) are very different from the Observed Body (OB).